Allusion to allegation the Supreme Court's history-making function in crystallizing the Marcos atrocities in Philippine History (2021)
While a nation's history has long been recognized as pivotal in the development of its legal system, the less often studied paradigm is the role a nation's legal system plays in the crystallization of its history. This Note argues that the Supreme Court of the Philippines, in failing to categorically recognize the human rights violations of the Marcos era, has shirked from the history-making function inherent in courts of law. The author highlights in particular how there has been unequal treatment in the recognition of Marcos as a
plunderer on one hand, and as a human rights violator on the other. Because of this, it is ultimately submitted that the Supreme Court has fallen short of its obligation of granting justice to the victims of
Martial Law.
Keywords: Martial law; Marcos, Ferdinand E. (Ferdinand Edralin), 1917-1989; Atrocities; Supreme Court. Philippines; Equality before the law